The Effect of Work Motivation and Indirect Compensation on Employee Performance: Study on Employees at an Educational Institution in The City of Bandung - Defri Aditya Nugraha; Vicky Achmad Zulfikar (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
Researchers conducted a study on the effect of motivation and indirect compensation on employee performance in an educational institution in Bandung. Moreover, this research analyzes the factor that has the most dominant influence between work motivation and indirect compensation on employee performance in one of the educational institutions in the city of Bandung. As many as 86 employees are the object of this study using a questionnaire. Based on research using path analysis, motivation, and indirect compensation variables in one of the educational institutions in the city of Bandung are declared valid. The conclusions and considerations related to the research results are paying attention to work motivation and indirect compensation to improve employee performance. The results of the study show that work motivation (X1) has a significant effect on employee performance (Y). Furthermore, indirect compensation (X2) significantly influences employee performance (Y). Therefore, work motivation (X1) and indirect compensation (X2) have a significant effect on employee performance (Y). To increase the motivation of administrative personnel in an educational institution in the city of Bandung, the leader should increase the firmness of attitude in making decisions, providing direction, guidance, instructions, and evaluation regarding the implementation of tasks and work to increase motivation. In addition, leaders must also be able to appreciate the results of the work of their subordinates because appreciation will make subordinates happy and more enthusiastic about working. Because by being appreciated, subordinates will also feel appreciated and acknowledge the importance of their existence for their leaders and the school. To increase the compensation of administrative personnel at an educational institution in the city of Bandung, the Leader should increase their compensation. To improve the performance of administrative staff at an educational institution in the city of Bandung, the agency should place more emphasis on administrative staff to pay full attention to the rules that the agency has implemented.